Comprehensive analysis of differential circular RNA expression in a mouse model of colitis‐induced colon carcinoma. Issue 12 (19th September 2018) - Yuan, Gang; Chen, Tingjia; Zhang, Haiqing; Cao, Qinghua; Qiu, Yun; Que, Biao; Peng, Sui; Chen, Minhu; Ji, Weidong
Abstract : Circular RNAs (circRNAs) have received increasing attention for their involvement in the pathogenesis of cancer; however, the characterization and function of circRNAs in colitis‐induced colon carcinoma remains largely unknown. A colitis‐induced colon carcinoma model was established in mice treated with azoxymethane‐dextran sodium sulfate (AOM‐DSS), and the circRNA profile was screened by next generation sequencing. Bioinformatic tools, including Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and network analysis were used to predict the functions of differentially expressed circRNAs and potentially coexpressed target genes. Among the detected candidate 3069 circRNA genes, 126 circRNAs were upregulated, and 108 circRNAs were down regulated in colon tissues from AOM/DSS mice compared to those from control mice. A total of six of these candidate circRNAs were validated by RT‐PCR. GO analysis revealed that numerous target genes including most microRNAs were involved in the Ras‐Raf‐MAPK pathway, actin cytoskeleton, focal adhesion, and additional biological processes. Our study revealed a comprehensive expression and functional profile for differentially expressed circRNAs in AOM/DSS induced colon carcinogenesis, indicating possible involvement of these dysregulated circRNAs in the development of colitis‐induced colon carcinoma. The mmu‐circ‐001226/mmu‐circ‐000287‐miRNA‐mRNA network may provide a potential mechanism for colitis‐associated colorectal cancer.